The impact of psychological well-being on academic performance among undergraduate dental students - Siddiqui, Muhammad Omer; Ali, Shabana; Yasmeen, Rahila; Shuja, Eruj; Siddiqui, Sana; Habib, Muhammad Farrukh (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the relationship between psychological wellbeing and academic performance among undergraduate dental students. Method: The analytical, cross-sectional study was done at a dental college in Rawalpindi, Pakistan, from January to July 2023, and comprised dental students after getting approval from Ethical Review Committee. Data on psychological wellbeing was collected using a short version of the Psychological Wellbeing Scale, assessing autonomy, environmental mastery, personal growth, positive relations with others, purpose in life, and self-acceptance. Academic performance data was obtained from the academic records. Data was analysed using SPSS 26. Results: Of the 210 students with mean age 23.8 ± 7.4 years, 158(75.2%) were females and 52(24.8%) were males. There were 151(71.9%) subjects who were second-generation medical students, while 59(28.1%) were first-generation students. There was a significant positive correlation between psychological wellbeing and academic performance (r= 0.55, p<0.05). Females outperformed the male students (p<0.05). Students who reported higher levels of satisfaction with the institution exhibited improved academic performance (p<0.05). Conclusion: Promoting wellbeing and providing support for students' emotional and psychological needs should be integral components of dental education. Key Words: Academic performance, Psychological wellbeing, Undergraduate dental students.